(untitled) (Al-Aasar, 2025)
This research article aims to challenge the commonly held misconception that pre-Islamic Arabs were unfamiliar with writing and literacy. The article explores the development and use of writing among the Arabs before the advent of Islam by paying attention on historical sources, archaeological findings, and classical narrations. It highlights various forms of written communication such as contracts, poetry, inscriptions, and religious texts that were prevalent in Arab society. The study examines the origins and evolution of Arabic script, tracing its roots to the Nabataean script and its later transformation into early Kufic and Heeri styles. Furthermore, it identifies key individuals and tribes who played a significant role in the propagation of writing in Arabia. The core objective of this article is to demonstrate that literacy was indeed a significant and functional part of Arab civilization, and that the Arabs possessed both oral and written traditions prior to Islam.